HUBUNGAN ANTARA KOORDINASI MATA-TANGAN DAN KECEPATAN REAKSI DENGAN KETERAMPILAN BERMAIN TENIS MEJA - Syahrianursaifi Syahrianursaifi; Yulinar Yulinar; Salbani Salbani (Jurnal Dedikasi Pendidikan, 2020)
The study, entitled "The Relationship between Eye-Hand Coordination and Reaction Speed with the Ability to Play Table Tennis (Research at the Young Indonesian Table Tennis Club Athlete of Banda Aceh City 2019) '' discusses the problem of the relationship between hands and speed of assistance with playing tennis table. This study discusses to study the relationship between eye-hand coordination and reaction speed with table tennis playing skills. The population in this study was the Banda Aceh Young Indonesian Club athlete who supported 30 people. The population is relatively small, then all members of the population are sampled as a study (total sampling). Data processing is done using simple analysis and multiple conversion analysis. The results obtained are as follows; (1) There is a positive and significant relationship between hand-playing skills and table tennis (R = 0.96), coordination contributes 92.16% to table tennis playing skills, (2) related to a positive and significant relationship between speed reaction with table tennis playing skills (R = 0.90), reaction speed contributed 0.81% to table tennis playing skills, and (3) Together with table tennis playing skills (R = 0.97). This shows that 94.09% variation in playing tennis skills is determined by the independent variables together.